Roles of Long‐Chain Alkylamine Ligands in Triple‐Halide Perovskites for Efficient NiOx‐Based Inverted Perovskite Solar Cells. Issue 6 (17th February 2022) - Ju, Hui; Ma, Yajie; Cao, Ye; Wang, Zixuan; Liu, Liming; Wan, Meixiu; Mahmoudi, Tahmineh; Hahn, Yoon-Bong; Wang, Yousheng; Mai, Yaohua
Abstract : The passivation of perovskite bulk and heterointerface defects is one of the most significant ways to enhance the efficiency and operational stability of perovskite solar cells (PSCs). So far, ammonium‐based alkylamine halides have been considered as effective passivation materials to reduce defects of the perovskite absorber layer. Herein, roles of long‐chain alkylamine ligands (LALs) in triple‐halide perovskites are systematically studied for achieving efficient NiO x ‐based inverted PSCs. Two kinds of LALs oleylammonium (OAm) and phenethylammonium (PEA), as perovskite bulk and interface passivation agents, respectively, are introduced. It is found that both OAm and PEA ligands cannot only assist their crystal growth with vertical orientation, but also suppress triple‐halide perovskite bulk and interface defects. As precursor additives, OAm ligands can be used as organic spacers to assist the generation of the 2D@3D perovskite bulk crystals. 2D@3D/2D perovskite heterostructures are further formed when the 2D@3D perovskite bulk film is post‐treated by PEA ligands. As a result, such strategies enable hysteresis‐free and highly efficient NiO x ‐based triple‐halide inverted PSCs. Abstract : Perovskite bulk and heterointerface defects that induce non‐radiative recombination and trap‐density in inverted perovskite solar cells (PSCs) can be suppressed by long‐chain alkylamine ligands passivation. The oleylammonium and phenethylammonium ligands act as orgainc spacers to assist growth of perovskite crystals, and suppress bulk, surface, grain boundaries, and buried interfaces defects. Thus, such strategies enable hysteresis‐free and efficient NiO x ‐based inverted PSCs.